SCAPE : identification of triggers and preservation watch component architecture, subcomponents and data model - Duretec, Kresimir (2012)
The SCAPE project is set to advance the planning and control of preservation operations from ad-hoc decision making to a continuous management activity. This document lays out a key component for this improvement. In Automated Watch, the project will provide automated mechanisms to support the monitoring and evolution of preservation plans over the lifecycle of digital content and react to a dynamically changing environment and user behaviour. Plan enactment and continuous operations need to be monitored. The collected measurements need to be analysed automatically to trigger appropriate events. Finally, critical changes in the technological environment should be detected and lead to automated notifications that can trigger decision making.